2013
DOI: 10.1158/1078-0432.ccr-12-3115
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of CD33 Nonsynonymous Single-Nucleotide Polymorphisms in Pediatric Patients with Acute Myeloid Leukemia Treated with Gemtuzumab-Ozogamicin–Containing Chemotherapy

Abstract: Purpose Purpose of this study was to evaluate clinical implications of CD33 SNPs in pediatric acute myeloid leukemia (AML) patients treated with gemtuzumab ozogamicin (GO) based therapy. Experimental Design We genotyped four CD33 SNPs: rs35112940 (G>A; Arg304Gly), rs12459419 (C>T; Ala14Val), rs2455069 (A>G; Arg69Gly) and rs1803254 (G>C; 3′UTR) in pediatric patients undergoing induction chemotherapy containing GO (COG-AAML03P1 trial; n=242) or not containing GO (St. Jude AML02 trial; n=172). Results CD33 SN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 14 publications
0
53
1
Order By: Relevance
“…This finding is encouraging given that several CD33 SNPs occur relatively commonly in AML patients and may impact the efficacy of CD33-targeted therapeutics, as recently suggested by analyses of pediatric patients treated with GO-containing multiagent chemotherapy. 16 It is well established that ABC transporter activity, in particular mediated by Pgp, is associated with poor prognosis and failure of conventional chemotherapeutics in AML. 29,30 Several studies have also demonstrated that expression of Pgp is a major factor contributing to clinical resistance to GO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is encouraging given that several CD33 SNPs occur relatively commonly in AML patients and may impact the efficacy of CD33-targeted therapeutics, as recently suggested by analyses of pediatric patients treated with GO-containing multiagent chemotherapy. 16 It is well established that ABC transporter activity, in particular mediated by Pgp, is associated with poor prognosis and failure of conventional chemotherapeutics in AML. 29,30 Several studies have also demonstrated that expression of Pgp is a major factor contributing to clinical resistance to GO.…”
Section: Discussionmentioning
confidence: 99%
“…16 To investigate the effect of these SNPs on AMG 330-induced cytotoxicity, we generated sublines of KG-1a cells transduced with mutant forms of CD33 corresponding to the clinically observed CD33 SNPs. When directly comparing sublines expressing equal levels of either wild-type CD33 or these CD33 SNPs, we did not detect any noticeable difference in the activity of AMG 330 (supplemental Figure 3).…”
Section: Effect Of Cd33 Expression and Cd33 Single Nucleotide Polymormentioning
confidence: 99%
“…76 Therefore, the impact of GO may need to be revisited in the light of concomitant mutations and single-nucleotide polymorphisms in CD33 that might affect treatment response. 77 Similarly, based on 2 controversial reports the potential benefit of all-trans retinoic acid (ATRA) in NPM1 mutated / FLT3-ITD negative patients remains elusive, but a recent AMLSG study in younger AML patients again suggests a beneficial effect. 78,79 FLT3 inhibitors.…”
Section: Runx1 Mutationmentioning
confidence: 99%
“…However, in 2010, Mylotarg was withdrawn from the market because a post-approval clinical trial demonstrated no benefit of adding Mylotarg to the standard chemotherapy for AML, coupled with a greater number of adverse events in the Mylotarg-treated group [9,21]. Nevertheless, retrospective analysis of clinical outcomes has indicated that the efficacy of Mylotarg treatment is influenced by polymorphisms of CD33 (Box 1), which likely decreases its overall effectiveness in total patient populations [22]. Accordingly, renewed efforts are underway to develop next generation antibody-based therapeutics to target CD33 for treatment of AML (Table 1).…”
Section: Antibody-based Targeting Of Siglecsmentioning
confidence: 99%
“…The allele is associated with apparently reduced CD33 expression level, because most anti-CD33 antibodies recognize Ig1 [105]. Interestingly, the same allele is associated with favorable outcomes in the pediatric AML patients treated with Mylotarg [22]. The CD33 allele carried by AML and LOAD patients will surely need to be considered in the development of future therapeutics.…”
Section: Figurementioning
confidence: 99%